2014
DOI: 10.1111/imm.12256
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor gamma agonists in the prevention and treatment of murine systemic lupus erythematosus

Abstract: Summary Peroxisome proliferator‐activated receptor gamma (PPARγ) agonists are known to have many immunomodulatory effects. We have previously shown that the PPARγ agonist rosiglitazone is beneficial when used early in prevention of disease in murine models of systemic lupus erythematosus (SLE) and SLE‐related atherosclerosis. In this report, we demonstrate that another PPARγ agonist, pioglitazone is also beneficial as a treatment for early murine lupus, indicating that this is a class effect and not agent‐spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…A recent study suggested that PPAR‐γ agonists could be used in the prevention and treatment of murine SLE. Oxer et al .…”
Section: Introductionmentioning
confidence: 70%
“…A recent study suggested that PPAR‐γ agonists could be used in the prevention and treatment of murine SLE. Oxer et al .…”
Section: Introductionmentioning
confidence: 70%
“…We also tested the efficacy of LXR Recent work suggested that PPARγ agonist treatment started before disease onset demonstrated the marked amelioration of disease, while it was not effective when started after disease onset [8]. We thought that the administration of LXR or PPARγ/δ agonists at 8 weeks of age might be too late to suppress the disease and we administered them immediately after the injection of pristane in BALB/c mice; however, they did not reveal the beneficial effects in prevention.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in regulating fat cell differentiation, lipid storage, and differentiation of monocytes into macrophages [32,33]. PPARs have, due to their immune regulatory functions, been linked to several autoimmune diseases, i.e., multiple sclerosis [34], lupus erythematosus [35], autoimmune thyroiditis [36], Graves ophthalmopathy [37], rheumatoid arthritis [38], psoriasis [39], and Guillain-Barré [40]. Similarly, PPARs have also been suggested as targets to treat chronic inflammatory diseases [20,41].…”
Section: Pparsmentioning
confidence: 99%